Pengaruh Pengetahuan Akuntansi dan Motivasi Kerja Terhadap Kinerja UMKM dengan Penggunaan Informasi Akuntansi Sebagai Variabel Mediasi (Studi pada Pelaku UMKM di Kabupaten Gresik) - Shalsabilla Dea Amanda; Suwandi Suwandi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to examine the effect of Knowledge Accounting and Work Motivation on MSME Performance with the Use of Accounting Information as a Mediating Variable in Gresik Regency. This type of research is quantitative research. The population of this study is MSME players in Gresik Regency. The sampling method in this study was purposive sampling method, namely a sample based on predetermined criteria and obtained 92 MSME as respondents. The data used in thisstudy are primary data using a questionnaire. The data analysis method used is the Partial Least Square ((PLS) method using SmartPLS 3.0 software. The result of this study indicate that accounting knowledge affects the use of accounting information, work motivation has no effect on the use of accounting information, accounting knowledge and work motivation have no effect on MSME performance, the use of accounting information affects the performance of MSMEs, accounting knowledge mediated by the use of accounting information affects the performance of MSMEs and work motivation mediated by the use of accounting information has no effect on MSME performance.